Tinjauan Literatur : Penerapan Business Intelligence untuk Meningkatkan Kinerja Bisnis Ekspedisi - Alfin Aulia Rachman; Jeni Susyanti (Publikasi Inspirasi Indonesia, 2024)
The purpose of this study is to explain the important role of Business Intelligence (BI) in improving the efficiency, productivity, and competitiveness of companies in a competitive market environment. The benefits of the results of this research can provide valuable insights for companies to use BI effectively to increase productivity, reduce operational costs, and achieve sustainable business growth. The research method applied is a qualitative approach using a literature study that focuses on the Business Intelligence domain. BI-related journal articles were analyzed using the PoP publication search tool. The findings of the research show that Business Intelligence (BI) has a very important role in improving the efficiency, productivity, and competitiveness of companies in a competitive market. Through comprehensive data analysis, BI helps companies to adapt more quickly to market changes, understand their operations better, and make more accurate decisions.